`int 5x/(e^(2x)) dx` Find the indefinite integral

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Recall that indefinite integral follows `int f(x) dx = F(x) +C` where:

`f(x)` as the integrand function

`F(x)` as the antiderivative of f(x)

`C` as the constant of integration.

 For the given  integral problem: `int5 x/e^(2x) dx` , we may  apply Law of exponent: `1/x^n =x^(-n)` then `1/e^(2x) = e^(-2x)` .

 `int5 x/e^(2x) dx =int5 x*e^(-2x) dx`

Apply the basic integration property: `int c*f(x) dx = c int f(x) dx` .

`int5 x*e^(-2x) dx= 5int x*e^(-2x) dx`

Apply integration by parts: `int f *g' = f*g - int g *f'du` .

Let :   `f =x` then `f' = dx`

          `g'=e^(-2x) dx` then` g = -1/2e^(-2x)`

Note:  `g = int g'= int e^(-2x) dx` . Apply u-substitution using `u =-2x` then `du = -2dx` or `(du)/(-2) =dx` .

`int e^(-2x) dx =int e^(u) * (du)/(-2)`

                      `= -1/2 int e^u du`

                      `= -1/2 e^u`

Plug-in `u =-2x` on `-1/2 e^u` , we get:   `int e^(-2x) dx =-1/2 e^(-2x)` .

 

Following the formula for integration by parts, we set it up as:

`5int x*e^(-2x) dx =5[ x*(-1/2 e^(-2x)) - int (-1/2 e^(-2x)) dx]`

                             `=5[ x*(-1/2 e^(-2x)) - (-1/2) int ( e^(-2x)) dx]`

                             `=(-5xe^(-2x))/2 + 5/2int ( e^(-2x)) dx`

Plug-in `int e^(-2x) dx =-1/2 e^(-2x)` , we get:

`5int x*e^(-2x) dx=(-5xe^(-2x))/2 + 5/2int ( e^(-2x)) dx`

                              `=(-5xe^(-2x))/2 + 5/2*[-1/2 e^(-2x)] +C`

                             ` =(-5xe^(-2x))/2 - (5 e^(-2x))/4 +C`

                            or   `(-5x)/(2e^(2x)) - 5/(4 e^(2x)) +C`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial